Nation-Building and History Education in a Global Culture
XIX, 197 p. 4 illus.
Keywords: This book examines the nexus between nation-building and history education globally and the implication for cultural diversity and social justice. It studies some of the major education reforms and policy issues in history education in a global culture, and regards them in the light of recent shifts in history education and policy research. In doing so, the volume provides a comprehensive picture of the intersecting and diverse discourses of globalisation, history education and policy-driven reforms. It makes clear that the impact of globalisation on education policy and reforms is a strategically significant issue for us all. The book focuses on the importance of nation-building and patriotism in history education, and presents up-to-date research on global trends in history education reforms and policy research. It provides an easily accessible, practical yet scholarly source of information about the international concerns in the field of globalisation, history education and policy research.